2022
DOI: 10.1088/1742-6596/2267/1/012155
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Band Structure calculation of Wurtzite CdS Using GGA and GGA+U functionals

Abstract: The wurtzite (wz) structure of CdS is analysed using density functional theory within the generalized gradient approximation (GGA) and Hubbard correction (GGA+U). The total energy convergence evaluation is carried out concerning energy cut-off (ecutwfc) and k-point sampling. The geometry optimization of wz-CdS is calculated using the total energy and force minimization process, which is based on the Broyden-Fletcher-Goldfarb-Shanno (BFGS) optimization algorithm. Bulk modulus and lattice parameters are estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The electronic structure of Ba near the (11−20) surface is investigated, where the densities of states (DOS) are computed and shown in Figure 8 for different concentrations. As shown in Figure 8a, HSE06 calculation results of the DOS plot and the band structure (not shown here) for the pure CdS surface with the band structure reported in previous theoretical works 54 can be found in the form of a direct band gap at the Γ-point. It is observed that the highest occupied state of the CdS surface is mainly derived from the S 3s states, while the lowest unoccupied state is generated from the Cd 5s and Cd 4p states.…”
Section: Resultsmentioning
confidence: 99%
“…The electronic structure of Ba near the (11−20) surface is investigated, where the densities of states (DOS) are computed and shown in Figure 8 for different concentrations. As shown in Figure 8a, HSE06 calculation results of the DOS plot and the band structure (not shown here) for the pure CdS surface with the band structure reported in previous theoretical works 54 can be found in the form of a direct band gap at the Γ-point. It is observed that the highest occupied state of the CdS surface is mainly derived from the S 3s states, while the lowest unoccupied state is generated from the Cd 5s and Cd 4p states.…”
Section: Resultsmentioning
confidence: 99%
“…When the U eff values of Zn and Cd were higher than 7.0 and 4.0 eV, the bandgap ZnCdS trends to be stable. Therefore, the Coulomb interaction U eff values were set to 7.0 and 4.0 eV to describe the 3 d electrons of Zn and 4 d electrons of Cd, respectively, which are also consistent to the literature 64 , 65 .…”
Section: Methodsmentioning
confidence: 92%
“…However, the PBE functional’s bandgap estimation was lower than the experimental values. To improve the accuracy, GGA+U was applied in the DFT calculation, introducing the Hubbard-U parameter to Cd-d and S-p orbitals for CdS and In-d for In 2 O 3 . , The CdS lattice parameters are 5.88 Å (JCPDF database:00–001–0783), while those for In 2 O 3 are 10.17 Å (JCPDF database: 00–001–0929). To minimize lattice mismatch between CdS and In 2 O 3 surfaces, a 1.73 × 1 supercell for CdS with lattice parameters of 10.17 Å, matching with In 2 O 3 surface lattice, was utilized by using VESTA software .…”
Section: Methodsmentioning
confidence: 99%
“…However, the PBE functional's bandgap estimation was lower than the experimental values. To improve the accuracy, GGA +U was applied in the DFT calculation, introducing the Hubbard-U parameter to Cd-d and S-p orbitals for CdS and In-d for In 2 O 3 36,37. The CdS lattice parameters are 5.88 Å (JCPDF database:00−001− 0783), while those for In 2 O 3 are 10.17 Å (JCPDF database: 00−001− 0929).…”
mentioning
confidence: 99%